Masivní enteroragie jako první príznak divertikulární choroby tracníku - Krska, Z; Klofanda, J; Pesková, M; Schmidt, D; Sváb, J; Melechovský, D; Kormanová, K (Rozhledy v chirurgii, 2001)
Retrospective and prospective analysis of massive enterorrhagia (m.e.). The aim of the study is the analysis of frequent causes of m.e--diverticular disease of the colon (DDC). The total number of patients with m.e. was 154 and the proportion of DDC in this total group was 17%, i.m. 24 patients. The total number of patients with the acute symptomatic DDC was 198 and the proportion of haemorrhagic DDC in this total group was 13.3%. The dominant form is conservative therapy (88.4%), surgical therapy was performed in 11.6% of cases. Discontinuous types of operations predominated. The analysis of the group and comparison with problems of m.e. in the literature.
Keywords: Aged; retrospektivní studie; Humans; divertikl tlustého střeva; Acute Disease; senioři; lidé; gastrointestinální krvácení; prospektivní studie; Gastrointestinal Hemorrhage; Retrospective Studies; akutní nemoc; Diverticulum, Colon; Prospective Studies